2017
DOI: 10.1155/2017/5843851
|View full text |Cite
|
Sign up to set email alerts
|

Social Skills Intervention Participation and Associated Improvements in Executive Function Performance

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by impairments in social communication. It has been postulated that such difficulties are related to disruptions in underlying cognitive processes such as executive function. The present study examined potential changes in executive function performance associated with participation in the Social Competence Intervention (SCI) program, a short-term intervention designed to improve social competence in adolescents with ASD. Laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 68 publications
1
15
1
2
Order By: Relevance
“…The lower performance of the ASD group on the three span tasks also replicates existing studies documenting diminished short-term recall in ASD [Alloway et al, 2016;Bowler et al, 2016;Christ et al, 2017;Poirier et al, 2011] and support the second aim of the present study, which was to provide further evidence that the well-documented ASD-related LTM difficulties [Desaunay et al, 2020;Boucher et al, 2012;Boucher & Bowler, 2008;Ben Shalom, 2003;Minshew & Goldstein, 1993] extend to STM span. However, the lack of a significant Group by Task interaction and the overlapping effect size confidence intervals for the three span tasks do not support the hypothesis that ASD individuals experience greater difficulty on more complex memory tasks [Minshew & Goldstein, 1998;Minshew et al, 2000;Williams et al, 2006aWilliams et al, , 2006b.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The lower performance of the ASD group on the three span tasks also replicates existing studies documenting diminished short-term recall in ASD [Alloway et al, 2016;Bowler et al, 2016;Christ et al, 2017;Poirier et al, 2011] and support the second aim of the present study, which was to provide further evidence that the well-documented ASD-related LTM difficulties [Desaunay et al, 2020;Boucher et al, 2012;Boucher & Bowler, 2008;Ben Shalom, 2003;Minshew & Goldstein, 1993] extend to STM span. However, the lack of a significant Group by Task interaction and the overlapping effect size confidence intervals for the three span tasks do not support the hypothesis that ASD individuals experience greater difficulty on more complex memory tasks [Minshew & Goldstein, 1998;Minshew et al, 2000;Williams et al, 2006aWilliams et al, , 2006b.…”
Section: Discussionsupporting
confidence: 90%
“…Our second aim is to determine whether or not the LTM difficulties seen in ASD, particularly diminished recall and poorer memory for more complex material are also mirrored in Lecouvey et al's set of STM tasks. Our prediction is that the ASD participants should show diminished performance on the Verbal, Visuospatial, and Multimodal span tasks and that the difference would be greater on the last two of these tasks compared to the first, principally because of existing findings of greater ASD‐related difficulty on spatial WM tasks [Alloway, Seed, & Tewolde, 2016; Christ et al, 2017; Steele, Minshew, Luna, & Sweeney, 2007, but see Desaunay et al, 2020] but also because the last two tasks involve a greater number of cognitive operations [Steele et al, 2007; Williams, Goldstein, Carpenter, & Minshew, 2005]. Our third aim is to use Lecouvey et al's Multimodal Integration task to test whether ASD individuals show the same difficulties with the episodic buffer as they found with an older typical sample.…”
Section: Introductionmentioning
confidence: 97%
“…According to the findings, this assumption was not approved. This finding was not consistent with the previous studies [24][25][26]. For explaining this finding, it can be said that improving social skills through some training sessions is partly impossible; also, the non-significant effects of cognitive rehabilitation on the social skills does not mean that such intervention is not useful rather it implies that targeting the underlying mechanism of social skills (adaptive behavior and executive functions) should be addressed early and for long period, as well as in a continuous way, since this population show the improvement of social skills in different settings.…”
Section: Discussioncontrasting
confidence: 99%
“…When children with poor executive functions experience problems in social interaction, they are separated from peers and may experience other difficulties in a particular situation [23]. Previous studies investigated the social skills training of this population and reported positive consequences [24][25][26]. So, there is a necessity to understand the best intervention to improve executive functions and the social skills of this population to improve their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, peer-based interventions have leveraged natural opportunities for peer interactions in school settings to successfully overcome high student-to-staff ratios and teacher burden (Bouffard and Little, 2003; Fantuzzo et al, 2005). However, few studies have begun to assess the efficacy of peer-based interventions in improving EFs (Christ et al, 2017).…”
Section: Discussionmentioning
confidence: 99%